Management of Adnexa Foreign Body: A Piece of Mica from a Broken Helmet - Windya Tri Hapsari; Ratna Doemilah (Vision Science and Eye Health Journal, 2022)
Introduction: Adnexa foreign body is one of the classifications of extraocular foreign body. Visual prognosis depends on the zone of injury, type, and size of the foreign body and subsequent complications. Case Presentation: A 5-year-old girl came to the outpatient clinic with her parent with chief complaints of swelling and pain in the lower eyelid in the left eye after she had a motorcycle accident with her parent (single accident) five months ago. At the time, the patient was hit by a piece of mica from a broken helmet in her left eye, and the patient complained that her left eye was red swollen and that she had difficulty opening her eyes and; when the midwife then referred her to an ophthalmologist in Jember and referred to Soetomo with diagnosis conjunctival tumor in LE. Visual acuity RLE 5/5, and in the conjunctiva, there was hyperemia and foreign body like glass or mica in fornix inferior. In the CT scan, there was foreign body or corpus alienum with size 1.05 x 0.5 x 2.1 cm in cutan subcutan left inferior eyelid until ciliary body and swelling in tissue around corpus alienum. The patient was the plan to extract the foreign body. Conclusion: Adnexa foreign body is one emergency case in ophthalmology. The extraction technique depends on the object’s composition and size because it impacts the step of the operation technique.